2020
DOI: 10.1002/jmv.26352
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection in persons living with HIV: A single center prospective cohort

Abstract: Summary Background Information about SARS‐CoV‐2 infection in HIV‐infected individuals is scarce. Methods In this prospective study, we included HIV‐infected individuals (PLWHIV) with confirmed SARS‐CoV‐2 infection and compared them with PLWHIV negative for SARS‐CoV‐2. Results we compared 55 cases of SARS‐CoV‐2 infection with 69 asymptomatic PLWHIV negative for SARS‐CoV‐2 RT‐PCR and/or serology. There was no significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
(57 reference statements)
2
37
0
1
Order By: Relevance
“…In any case, data presented herein are in line with the greater clinical severity of this disease among HIV-infected patients suggested by studies conducted in South Africa 8 or in Italy 21 .…”
Section: Discussionsupporting
confidence: 89%
“…In any case, data presented herein are in line with the greater clinical severity of this disease among HIV-infected patients suggested by studies conducted in South Africa 8 or in Italy 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Despite these optimistic findings, the lack of higher risk for severe COVID‐19 in PLWH has been recently questioned by several studies reporting worse outcomes in HIV‐positive subjects compared to the general population, and particularly in frailer subgroups as elderly, 4,13,14 patients with underlying comorbidities, 14,15 more severely immunosuppressed patients, 13,14 and black people 16 . Indeed, older age and comorbidities, already identified as risk factors for severe disease in the general population, have been clearly related to a greater risk of both acquiring and having a severe clinical course of COVID‐19 also in PLWH 4,13–15 . Notably, several studies have reported a significant correlation between age and disease severity, 14 with a greater risk of morbidity and mortality for COVID‐19 in the older age strata of the HIV‐positive population compared to the general population 4,13 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Indeed, older age and comorbidities, already identified as risk factors for severe disease in the general population, have been clearly related to a greater risk of both acquiring and having a severe clinical course of COVID-19 also in PLWH. 4,[13][14][15] Notably, several studies have reported a significant correlation between age and disease severity, 14 with a greater risk of morbidity and mortality for COVID-19 in the older age strata of the HIV-positive population compared to the general population. 4,13 The premature aging and the premature burden of age-related diseases due to the chronic immune activation, which characterizes HIV-positive subjects, might probably explain these results.…”
mentioning
confidence: 99%
“…However, Suwanwongse et al observed the clinical features and outcomes of nine HIV/SARS-CoV-2 coinfected patients and found that low CD4 + T cell counts in the HIV-positive patients may adversely affect the COVID-19 outcomes [14]. Maggiolo compared 55 cases of SARS-CoV-2 infection with 69 asymptomatic people living with HIV (PLHIV) negative for SARS-CoV-2 RT-PCR and/or serology, and suggested that HIVpositive individuals are not protected from SARS-CoV-2 infection or have a lower risk of severe disease and those with low CD4 + T cell counts might have worse outcomes [15]. Studies also suggested that HIV-positive individuals should not be considered to be protected from SARS-CoV-2 infection or to have lower risk of severe disease [16,17].…”
Section: Resultsmentioning
confidence: 99%